(3eONd dYde GdGbJUGO (B/s - (3Hf MehO, ScjfIs ((3GdLRGFQ(B: s (3OGQ GdeMeOjI(B, s, 2009)
(3JYQja Yde GdGbJUGO , JWhQg , ehVhYg , efgLg h YdGbJg HGdYdhe GdGNQi , GdYhGed GdeDOjI dfTCI GdeTcdI GdGbJUGOjI , GdMGLGJ GdGfSGfjI ceMQc ddfTGW GdGbJUGOj , GdehGQO GdGbJUGOjI chSjdI dETHGY GdMGLGJ GdGfSGfjI , Md GdeTcdI GdGbJUGOjI , fTCI GdfbhO eGgjJgG ,CfhGYgG h GdfXQjGJ GdfbOjI , eaghe GdShb , GdWdH ,GdYQV , JMOjO GdSYQ MSH CTcGd GdShb GdCSGSjI , GdJWhQ GdJGQjNj dfXQjI GdJLGQI GdOhdjI ,IfXQjI GdJLGQI GdOhdjI MSH GdcdGSjc h MSH GdfjhcdGSjc , GdfXQjI GdMOjKI aj GdJLGQI GdOhdjI , JhRjY GdeOGNjd (B: (3GdCLhQ , GdQjY GdYbGQj , GdQHM, GdaGFOI , GdeMGSHI GdhWfjI (B: (3GdeaGgje GdCSGSjI ddONd GdhWfj , bjGS GdONd GdhXfj HWQjbI GdGfJGL h HWQjbI ONhd YhGed GdGfJGL h Ydi CSGS WQjbI GdGfaGb , JYQja GdJVNe h GdJMdjd GdacQj dg , CdBKGQ GdeJQJHI Ydi GdJVNe h eYGdLJg , GdfXGe GdfbOj GdOhdj , UfOhb GdfbO GdOhdj h GdHfc GdOhdj ddEfTGA h GdfYejQ , GdefXeI GdOhdjI ddJLGQI h GdJYQjaGJ GdLeQcjI h GdefXeI GdYGdejI ddJLGQI , GdJcJdGJ GdGbJUGOjI GdOhdjI , GdJMLQHI GdChQhHjI aj GdJYGhf h GdJcGed GdOhdj , GdJcGed GdGbJUGOj Hjf GdOhd GdYQHjI , GdJLGQH GdShajGJjI h GdGeQjcjI h GdBSjhjI aj GdJYGhf h GdJcGed GdGbJUGOj(B.s
(3eQGLY U(B.256s
Keywords: (3GdGbJUGOs; (3GdJVNes; (3GdShbs; (3GdeTcdI GdGbJUGOjIs; (3GdfbhOs; (3Yde GdGbJUGOs